Fiocruz as an actor in Brazilian foreign relations in the context of the Community of Portuguese-Speaking Countries: an untold story - Alejandra Carrillo Roa; Felipe Ricardo Baptista e Silva (História, Ciências, Saúde: Manguinhos, 2015)
Brazilian foreign policy paradigms and changes in the global scenario since the Cold War created conditions for stronger ties between Brazil and Portuguese-speaking African countries. Recently, Brazil took the lead in regional integration processes and in South-South cooperation initiatives. These strategies and Fiocruz's acknowledged technical expertise resulted in its direct involvement in Brazilian foreign public health policy in the Community of Portuguese-Speaking Countries. Fiocruz developed cooperation projects in various areas, sharing its know-how and best practices in the most critical fields in partner countries, consolidating "public health framework cooperation" and contributing to diversifying Brazil's partners and promoting Brazil as a global actor.